The Specificity and Reliability of Conflict Adaptation: A Mouse-Tracking Study - Grundy, John G. (Frontiers in Psychology, 2022)
Researchers have recently begun to question the specificity and reliability of conflict adaptation effects, also known as sequential congruency effects (SCEs), one of the most commonly studied effects in cognitive psychology. Some have even used the lack of reliability across tasks (e.g. Flanker, and Stroop) to argue against models of cognitive control that have dominated the field for decades. The present experiment tested the possibility that domain-general processes across tasks might appear on more sensitive mouse-tracking metrics rather than overall reaction times. The relationship between SCE effects on the Stroop and Flanker tasks were examined for the first time using a mouse-tracking paradigm. Three main findings emerged: 1) Robust SCEs were observed for both the Stroop and Flanker tasks at the group level, 2) Within-task split-half reliabilities for the SCE across dependent variables were weak at best and non-existent in most cases, and 3) SCEs for the Flanker and Stroop tasks did not correlate with each other for overall reaction times, but did show significant correlations between tasks on more dynamic measures that captured processes before response execution. These findings contribute to the literature by highlighting how mouse-tracking may be a fruitful avenue by which future studies can examine the specificity and reliability of conflict adaptation and tease apart different theoretical models producing the effects.